Volumetric assessment of fat graft retention over implant by MRI - Emma K C Symonds; Heath Wilms; Carys Finlayson; Kathryn E Hally; Bianca Black; Sarah V Sparks; Angie Slocombe; Elizabeth R Dennett; Kirsty M Danielson; Ineke Meredith (Australasian Journal of Plastic Surgery)
**Background**: Autologous fat grafting (AFG) is an increasingly popular adjunct to post-mastectomy breast reconstruction as it can produce a natural cosmetic outcome and alleviate undesirable radiotherapy-associated consequences, with low surgical risk. However, graft retention rates are variable and unpredictable. In order to improve and understand what influences graft retention rates, accurate and consistent methods for the measurement of graft retention must be developed. **Methods**: Twenty patients who were undergoing AFG following a previous mastectomy were prospectively enrolled. Of these, six women suitable for immediate breast reconstruction (IBR) with implant underwent MRI pre- and three months post-AFG. **Results**: All patients had a net gain in volume at three months post-procedure with a mean of 123.6 ± 56.07cm^3^; however, the percentage retention ranged from 30.0 to 104.7 per cent. **Conclusions**: This study has demonstrated the feasibility of measuring AFG retention over implant using MRI, as well as confirming variable tissue retention rates. This is an important step forward for studies on improving overall graft survival.